Managing for results : - Nelson, Sandra S. (American Library Association, 2000)
The authors of Wired for the Future: Developing Your Library Technology Plan (Professional Media, LJ 6/1/99) have teamed up with Ellen Altman, author of numerous works on library administration, to produce this companion to the two-volume Planning for Results: A Public Library Transformation Process (Professional Media, LJ 6/15/98). If your library has gone through the planning for results process and you are unsure what to do next, this volume will help you gather the data on the resources you need to implement your plan. Topics addressed include an overview of resource allocation, specifics on managing staff, collections, and facilities, and a brief look at managing technology. For each of the management issues addressed, a series of reproducible workforms (with a permission notice on each) is included. As the authors point out frequently, if you do not yet know what you are trying to accomplish, then this is not the book for you. While written for public libraries, and specifically for those that have used the Planning for Results framework to identify priorities, this book has something to offer to any library making decisions about how to deploy, or redeploy, resources to accomplish specific results. Recommended for all public libraries and library science collections